2018
DOI: 10.1111/roiw.12399
|View full text |Cite
|
Sign up to set email alerts
|

Do Rising Top Incomes Spur Economic Growth? Evidence From OECD Countries Based on a Novel Identification Strategy

Abstract: We investigate the causal relationship between the growth rate of top income shares and economic growth in 12 OECD economies for the period 1950–2010. To analyze patterns of short‐ and long‐run causality, we build upon recent advances in structural‐vector autoregressive modeling of non‐Gaussian systems. This framework allows us to discriminate between rival transmission channels by means of dependence tests, since independent shocks are unique for a particular causation pattern. We consider the share of income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, there are instances where the relationship between economic growth and wage levels may be reversed. For example, economic growth may lead to higher wages at the top level but not at the middle level (Herwartz & Walle et al, 2020).…”
Section: Employment Level and Povertymentioning
confidence: 99%
“…However, there are instances where the relationship between economic growth and wage levels may be reversed. For example, economic growth may lead to higher wages at the top level but not at the middle level (Herwartz & Walle et al, 2020).…”
Section: Employment Level and Povertymentioning
confidence: 99%
“…Furthermore, Litschig and Lombardi (2019) present evidence that, in terms of the subsequent growth effects, it matters whether inequality or redistribution originates from the lower or upper tails of the distribution. Specifically, regarding top income, Herwartz and Walle (2020) have showed that an increase in the share of income that goes to the top 1 percent is related to higher economic activity. Focusing on 12 OECD economies in the post-1950 period, the main transmission channel lies in the prevailing structure of incentives.…”
Section: An Overview Of the Related Literaturementioning
confidence: 99%
“…The second group touches upon the opposite direction of the causality from inequality to growth (e.g., Persson and Tabellini (1994) and Alesina and Rodrik (1994), etc. ), as well as more recent variations on top income shares (Herwartz & Walle, 2020) and redistribution (El‐Shagi & Shao, 2019). The third group identifies determinants of economic growth or inequality (e.g., Barro (2000), etc.…”
Section: Introductionmentioning
confidence: 99%